Catalytic Low-Temperature Dehydration of Fructose to 5-Hydroxymethylfurfural Using Acidic Deep Eutectic Solvents and Polyoxometalate Catalysts - Körner, Sam; Albert, Jakob; Held, Christoph (Frontiers in Chemistry, 2019)
HMF synthesis typically requires high temperature and is carried out in aqueous solutions. In this work, the low-temperature dehydration of fructose to HMF in different deep eutectic solvents (DES) was investigated. We found a very active and selective reaction system consisting of the DES tetraethyl ammonium chloride as hydrogen bond acceptor (HBA) and levulinic acid as hydrogen bond donor (HBD) in a molar ratio of 1:2 leading to a maximum HMF yield of 68% after 120 hours at 323 K. The DES still contained a low amount of water at the initial reaction, and water was also produced during the reaction. Considering the DES properties, neither the molar ratio in the DES nor the reaction temperature had a significant influence on the overall performance of the reaction system. However, the nature of the HBA as well as the acidity of the HBD play an important role for the maximum achievable HMF yield. This was validated by measured yields in a DES with different combinations of HBD (levulinic acid and lactic acid) and HBA (choline chloride and tetra-n-alkyl ammonium chlorides). Moreover, addition of vanadium containing catalysts, especially the polyoxometalate HPA-5 (H8PV5Mo7O40) leads to drastically increased reaction kinetics. Using HPA-5 and the DES tetraethyl ammonium chloride – levulinic acid we could reach a maximum HMF yield of 57% after only 5 hours reaction time without decreasing the very high product selectivity.